Subsidizing the Adoption of Energy-Saving Technologies: Analyzing the Impact of Uncertainty, Learning and Maturation - Henri L.F. de Groot; Peter Mulder; Daan P. van Soest (Tinbergen Institute, 2004)
As part of the Kyoto Protocol, many countries have committed themselves tosubstantially reduce the emission of greenhouse gases within a politically imposed timeconstraint. Investment subsidies can be an important instrument to stimulate the adoption ofenergy-saving technologies to achieve emission reduction targets. This paper addresses theimpact of adoption subsidies on the amount of energy savings, taking into account endogeneityand uncertainty of technological progress. Neglecting these two characteristics oftechnological progress tends to result in overestimation of the short-run effectiveness ofinvestment subsidies, whereas the effects on long-run effectiveness are ambiguous.
Keywords: Q40; O32; 330; energy efficiency; investing under uncertainty; subsidies; learning; investment timing.; Energieeinsparung; Subvention; Energietechnik; Theorie